2009
DOI: 10.4102/sajr.v13i4.485
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating erect chest imaging in children, using the Lodox Statscan digital X-ray machine

Abstract: Background. Chest radiography accounts for a significant proportion of ionising radiation in children. The radiation dose of radiographs performed on the Lodox Statscan system has been shown to be lower than that of a computed radiography (CR) system. The role of the Lodox Statscan (subsequently referred to as the Statscan) in routine erect chest radiography in children has not been evaluated. Objective. To evaluate the image quality and diagnostic accuracy of erect paediatric chest radiographs obtained with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…1 5 8–10 12 13 17 22–24 26 All studies except one reported the assessor in charge of reviewing the radiography. The majority of studies used radiologists as their radiography assessors, and five of them used both clinical physicians and radiologists as their radiography assessors; the preliminary diagnosis was usually made by a physician and a definitive diagnosis was made by a radiologist.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 5 8–10 12 13 17 22–24 26 All studies except one reported the assessor in charge of reviewing the radiography. The majority of studies used radiologists as their radiography assessors, and five of them used both clinical physicians and radiologists as their radiography assessors; the preliminary diagnosis was usually made by a physician and a definitive diagnosis was made by a radiologist.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies evaluated the image quality, including three studies using reliability evaluation,13 17 22 two studies using attitude survey1 23 and one study using an equivalence scoring system (table 3). 26 In two pilot studies of paediatric patients with polytrauma,13 17 Lodox allowed superior visualisation of the trachea and main bronchi compared with computed radiograph, which afforded better visualisation of the right main bronchus by an average of 1.8 points and the left main bronchus by an average of 1.25 points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further study on erect chest radiography in the same institution on 33 children confirmed this and advocated the use of the Statscan in the diagnosis of childhood tuberculosis (TB), where airway narrowing occurs as a result of nodal compression [24]. Figure 5 shows a Lodox supine radiograph, illustrating the superior ability to visualise the major airways.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have reported on the use of the Lodox system for imaging in paediatric emergency wards [21, 24, 27, 3638]. In most of these situations, the system was used for traumatic emergencies, largely due to its dose-saving quality, and the particular benefit this has in paediatric cases [39], although Evangelopoulos et al [37] did not find this dose benefit in their study of 19 paediatric patients, possibly due to the inclusion of lateral full-body scans.…”
Section: Resultsmentioning
confidence: 99%